Forensic characterization of polycyclic aromatic hydrocarbons and hopanes in aerosols from Peninsular Malaysia - Bahry, Pourya Shahpoury; Zakaria, Mohamad Pauzi; Abdullah, Ahmad Makmom; Abdullah, Dzulkefly Kuang; Sakari, Mahyar; Chandru, Kuhan; Shahbazi, Azadeh (Taylor & Francis, 2009)
A forensic study on the characterization of polycyclic aromatic hydrocarbons (PAHs) and hopanes in atmospheric aerosols has been carried out on nine locations in peninsular Malaysia in July 2006. There were 18 individual PAHs and 16 individual hopanes detected in the samples. Total PAH concentrations ranged from 0.58 to 10.49 ng/m3, and hopanes ranged from 1.62 to 10.49 ng/m3. Source identification using diagnostic ratios suggests that the biomass burning and vehicular emissions are the main sources of PAHs in the samples. Additionally, the strong influence of crankcase oil incorporated in street dust was identified pointing out a significant source of hopanes in the study area.